The interaction of childhood maltreatment, sex, and borderline personality features in the prediction of the cortisol awakening response in adolescents - Kaess, Michael (Psychopathology, 2017)
Aims: The study aimed to investigate childhood maltreatment, sex, and borderline personality disorder (BPD) symptoms as prospective predictors of adolescent hypothalamic-pituitary-adrenal (HPA) axis reactivity. Method: A sample of 69 adolescents (30 female and 39 male) were selected from a larger longitudinal study of adolescent development and assessed at 3 time points. BPD symptoms were assessed at T1 (approx. 12.5 years), childhood maltreatment was assessed at T2 (approx. 14.9 years), and multiple assessments of salivary cortisol (cortisol awakening response; CAR) were undertaken at T3 (approx. 15.5 years). Results: Multivariate linear regression analysis revealed a significant main effect for childhood maltreatment but not for early BPD symptoms as a predictor of lower CAR in adolescence (p = 0.047). The association between childhood maltreatment and attenuated CAR was moderated by both early BPD symptoms (p = 0.024; no childhood maltreatment-dependent attenuation of CAR in the presence of BPD symptoms) and sex (p = 0.012; childhood maltreatment-dependent attenuation of CAR in females only). Furthermore, a 3-way BPD × childhood maltreatment × sex interaction (p = 0.041) indicated that the moderating effect of BPD symptoms was present in females only. Conclusion: These findings indicate that attenuation of the HPA axis occurs as a response to early maltreatment rather than being related to the early occurrence of BPD pathology. Traumatized female individuals with BPD symptoms might bypass adaptive HPA axis attenuation.
Gesehen am 31.07.2018
Published online: March 11, 2017